"Choose Your Own Adventure": Web-Based Case Studies of Inclusive Education as a Form of Professional Learning for School Principals. (March 2023) - Sider, Steve; Maich, Kimberly; Specht, Jacqueline; Treadgold, Carolyn; Winger, Hillary
We examine the process of developing web-based case studies, a novel form of professional learning for principals, specifically related to inclusive school leadership. Based on the input from 39 principals, 5 case studies were developed with branching scenarios that provided multiple options for decision-making. These "choose your own adventure" case studies were used in a special education for school administrators course with 109 participants in Ontario, Canada. We consider the authenticity of the cases, the importance of incorporating multiple perspectives, and issues related to function, form, and choice. We incorporate five lessons for developing web-based case studies.